Bibliometric analyses of social media for educational purposes over four decades - Yu, Zhonggen; Sukjairungwattana, Paisan; Xu, Wei (Frontiers in Psychology, 2023)
The unexpected outbreak of COVID-19 pandemic has led students to frequently use social media to receive education, which brought about both positive and negative learning outcomes (Oliveira, 2022). To address the issue of integrating social media into education, this study conducted both quantitative and qualitative studies using VOSviewer and CitNetExplorer. The qualitative study through CitNetExplorer, involving 1780 publications, concluded that while social media might have gained popularity in education based on the classic theoretical framework of the zone of proximal development, there might be many challenges such as teacher resistance, data privacy, costs, and ethical and social issues. Besides, this study conducted bibliometric analyses using VOSviewer (N = 1841) to identify the top cited authors, organizations, documents, references, sources, countries, and keywords with high occurrences based on the citation networks. In the future, researchers could enhance the studies on how to guide students and teachers to properly integrate social media into education.